2016
DOI: 10.1007/s00216-016-0035-6
|View full text |Cite
|
Sign up to set email alerts
|

QCM-based rupture force measurement as a tool to study DNA dehybridization and duplex stability

Abstract: The stability of double-stranded DNA (dsDNA) was assessed on the basis of unwinding force measurement. Unwinding force was measured directly with a quartz crystal microbalance (QCM). The amplitude of its surface oscillations was controlled by supplying variable alternate voltage. Under smoothly increasing amplitude of QCM surface oscillations, dsDNA fixed on QCM surface through one of its ends got unwound. This procedure allows reliable measurement of rupture force as small as 5-10 pN. It was demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In the present work, we continue to develop the procedure proposed by us previously. It was demonstrated that unwinding of the DNA double helix may be carried out with the help of quartz crystal microbalance (QCM). In particular, temperature dependence was studied previously . In the present work, we made an attempt to determine the height of the energy barrier.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the present work, we continue to develop the procedure proposed by us previously. It was demonstrated that unwinding of the DNA double helix may be carried out with the help of quartz crystal microbalance (QCM). In particular, temperature dependence was studied previously . In the present work, we made an attempt to determine the height of the energy barrier.…”
Section: Introductionmentioning
confidence: 95%
“…In particular, temperature dependence was studied previously. 20 In the present work, we made an attempt to determine the height of the energy barrier. To compare our data with the data available from literature and to verify our approach, we carried out parallel AFM-based measurements with our oligonucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…Probe hybridization techniques include northern blotting, in situ hybridization, and microarrays are well established but often require a large quantity of samples. Amplification technologies, including real‐time fluorescent quantitative polymerase chain reaction (RT‐PCR) and rolling circle amplification (RCA), are often time‐consuming and complicated to operate. Recently, the quartz crystal microbalance (QCM) mass sensor has the characteristics of high sensitivity, label‐free and, real‐time analysis, and it has been widely used in biosensors .…”
Section: Introductionmentioning
confidence: 99%
“…Amplification technologies, including real‐time fluorescent quantitative polymerase chain reaction (RT‐PCR) and rolling circle amplification (RCA), are often time‐consuming and complicated to operate. Recently, the quartz crystal microbalance (QCM) mass sensor has the characteristics of high sensitivity, label‐free and, real‐time analysis, and it has been widely used in biosensors . Many studies have shown that DNA‐modified QCM biosensors can be applied to detect such processes as DNA hybridization and single base mismatch of DNA .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation